Concept progression of high school students related to the concept of parallel electric circuits as the effect of applying CCROI integrated with T-ZPD strategy. (April 2020) - Basori, H; Suhandi, A; Kaniawati, I; Rusdiana, D
Abstract: The aim of study was to obtain an overview of the effects of application of conceptual construction-reconstruction oriented instruction (CCROI) using the Tetrahedral-ZPD (T-ZPD) strategy on the concept progression of high school students related to the concept of parallel electric circuits. The categories of concept progression reviewed included: consistent with scientific conceptions, progress well, not progress and degradation. A pre-experiment method with one group two conceptual test design was used in this research. The number of research subjects was 38 students consisting of 20 females and 18 males, in one of high schools in the West Bandung district of West Java province. Data were collected by conception test in the four-tier test format related to the concept of parallel electric circuits. The results showed that at the first conceptual test, the state of conception of the students are: scientific conception (8%), misconception (62%), and no conception (30%), whereas at the second conceptual test, the students' conception are: scientific conception (82%), misconception (13%), and no conception (5%). Based on the state of students' conception it can be determined the number of students in each category of concept progression as follows: consistent with scientific conceptions (8%), progress well (74%), not progress (18%) and degradation (0%). These results indicate that the implementation of CCROI with the T-ZPD strategy has high effectiveness in facilitating the achievement of the category of concept progression that progresses well.